Comparing veterinarians' attitudes to and the potential influence of pet health insurance in Austria, Denmark and the UK. (8th January 2022) - Springer, Svenja; Lund, Thomas Bøker; Grimm, Herwig; Kristensen, Annemarie T.; Corr, Sandra A.; Sandøe, Peter
Abstract: Background: Health insurance offers many benefits to clients and veterinarians, such as the ability to perform necessary and possibly cost‐intensive medical interventions without financial constraints, or to potentially prevent euthanasia based on financial challenges. However, concerns about negative consequences, such as the overuse of diagnostic tests or overtreatment, have also been raised. Methods: Using an online questionnaire distributed via e‐mail, which included a section on health insurance, we investigated the relative number of insured dogs and cats treated by Austrian, Danish and UK veterinarians (N = 636) and the attitudes of those veterinarians toward health insurance. Further, using a case vignette, we examined whether coverage by health insurance may influence treatment suggestions. Results: Even though veterinarians in all three countries believe that health insurance reduces stress since clients' financial resources will be less important, we found that Austrian veterinarians are more likely to agree that health insurance is unnecessary compared to Danish and UK veterinarians. Further, many raised the concern that insurance policies influence clinical decisions; and less than half supported the idea of making insurance mandatory. A majority of veterinarians in Austria and the UK thought that insurance can lead to the overuse of diagnostic tests, and in the UK a majority also thought that it can lead to overtreatment. Using case vignettes, we found that veterinarians were significantly more likely to suggest a CT scan to a client with an insured animal, in contrast to a client with stated financial limitations. Further, UK veterinarians were more likely to suggest a CT scan to a client with an insured animal, in contrast to a client without insurance. Conclusion: In conclusion, we found that veterinarians, in general, were in favour of health insurance, and that greater coverage may increase more cost‐intensive veterinary care. Our findings also raise a potential ethical challenge of health insurance causing differential access to clinical care for patients.